1987
DOI: 10.1007/bf00151227
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced gastric paresis

Abstract: A 27 year old male with metastatic testicular carcinoma was treated with cisplatin, vinblastine, and bleomycin (PVB) chemotherapy. After receiving a cumulative dose of 500 mg/m2 of cisplatin, he developed severe nausea and vomiting and had clinical evidence of a cisplatin-induced peripheral neuropathy. His vomiting resolved five weeks after discontinuation of cisplatin. We believe this case represents the first report of gastric autonomic neuropathy induced by cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…30 Other signs include gait disturbances due to defective proprioception, depressed tendon reflexes, decrease of vibratory, touch, and pain sensitivity, 39,40,45 and autonomic dysfunction. 4,9,40 Electrophysiological evaluations show slowing of sensory nerve conduction and reduction of the amplitude of the nerve action potentials, with minimal or absent motor involvement. 5,10,38,39 Slowing of central conduction velocity, measured by somatosensory evoked potentials, has been reported after cumulative doses of 200-400 mg/m 2 .…”
mentioning
confidence: 99%
“…30 Other signs include gait disturbances due to defective proprioception, depressed tendon reflexes, decrease of vibratory, touch, and pain sensitivity, 39,40,45 and autonomic dysfunction. 4,9,40 Electrophysiological evaluations show slowing of sensory nerve conduction and reduction of the amplitude of the nerve action potentials, with minimal or absent motor involvement. 5,10,38,39 Slowing of central conduction velocity, measured by somatosensory evoked potentials, has been reported after cumulative doses of 200-400 mg/m 2 .…”
mentioning
confidence: 99%
“…Chemotherapy-induced gastroparesis has been well recognized as a rare but careful complication with high-dose chemotherapy such as myeloablative regimens prior to bone marrow transplantation in blood cancers by several case reports ( 6 , 7 ). However, there is an only one case report of this disease in chemotherapy for solid cancer, which was published in 1980s ( 8 ). This report also suggested that gastroparesis might be an adverse event as a cumulative toxicity of platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy-induced gastroparesis has been recognized as a rare complication of high-dose chemotherapy such as myeloablative regimens prior to bone marrow transplantation in patients with blood cancers [5,6]. However, as far as we are aware, there is only one case report of this condition associated with chemotherapy for solid tumors [7]. This report from 1987 also suggested that gastroparesis might result from cumulative toxicity of platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%